Interspecific Analysis of Sea Urchin Adhesive Composition Emphasizes Variability of Glycans Conjugated With Putative Adhesive Proteins - Gaspar, Lisa; Flammang, Patrick; José, Ricardo; Luis, Ricardo; Ramalhosa, Patrício; Monteiro, João; Nogueira, Natacha; Canning-Clode, João; Santos, Romana (Frontiers in Marine Science, 2021)
Sea urchins possess specialized adhesive organs, tube feet. Although initially believed to function as suckers, it is currently accepted that they rely on adhesive and de-adhesive secretions to attach and detach repeatedly from the substrate. Given the biotechnological potential of their strong reversible adhesive, sea urchins are under investigation to identify the protein and glycan molecules responsible for its surface coupling, cohesion and polymerization properties. However, this characterization has only focused on a single species, Paracentrotus lividus. To provide a broader insight into sea urchins adhesion, a comparative study was performed using four species belonging to different taxa and habitats: Diadema africanum, Arbacia lixula, Paracentrotus lividus and Sphaerechinus granularis. Their tube feet external morphology and histology was studied, together with the ultrastructure of their adhesive secretory granules. In addition, one antibody and five lectins were used on tube foot histological sections and extracts, and on adhesive footprints to detect the presence of adhesion-related (glyco)proteins like those present in P. lividus in other species. Results confirmed that the antibody raised against P. lividus Nectin labels the adhesive organs and footprints in all species. This result was further confirmed by a bioinformatic analysis of Nectin-like sequences in ten additional species, increasing the comparison to seven families and three orders. The five tested lectins (GSL II, WGA, STL, LEL, and SBA) demonstrated that there is high interspecific variability of the glycans involved in sea urchin adhesion. However, there seems to be more conservation among taxonomically closer species, like P. lividus and S. granularis. In these species, lectin histochemistry and lectin blots indicated the presence of high molecular weight putative adhesive glycoproteins bearing N-acetylglucosamine residues in the form of chitobiose in the adhesive epidermis and footprints. Our results emphasize a high selective pressure for conservation of functional domains in large putative cohesive proteins and highlight the importance of glycosylation in sea urchin adhesion with indications of taxonomy-related conservation of the conjugated glycans.